Antimicrobial Activity of Achillea falcata Extracts Against some causative agents (Journal of the College of Basic Education, 2022)
The antibacterial and antifungal effects of aqueous and alcoholic extracts of Achillea falcata L. against different bacterial species (Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris,Salmonella typhi, Enterococcus faecalis, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogens, Bacillus cereus, Bacillus subtilis and fungal species (Candida albicans, Aspergillus flavus and Aspergillus niger) were studied. The results revealed that no activity of aqueous extract against both of G+Ve , G-Ve bacteria and fungi except weak activity against E. coli (8 mm of inhibition zone), while alcoholic extract showed varied activities against E. coli , K. pneumonia, Pro. Vulgaris, E. faecalis, S. aureus, B. cereus,C. albicans and A. flavus (24,25,12,12,22,10, 14,8) mm inhibition zones respectively except P. aeroginosa, S.typhi, S. epidermidis, S. pyogenes and B. subtilis. These results revealed that the alcoholic extract showed significant activity (at P £ 0.05) comparable with aqueous extract. The minimum inhibitory concentration (MIC) values of alcoholic plant extract for bacteria were ranged between 110-250 µg\ml , while it was 250µg\ml and 1000 µg\ml for both C. albicans and A.flavus respectivly.